Keteladanan Guru Dalam Membentuk Karakter Jujur Dan Disiplin Peserta Didik Kelas V Sd Negeri 6 Langgikima - Chairan Zibar L. Parisu (Jurnal Sultra Elementary School, 2022)
Teacher exemplarity plays a crucial role in instilling and shaping students’ honest and disciplined character. The objectives of this study are: (1) to describe the forms of teacher exemplarity in instilling honesty among fifth-grade students at SD Negeri 6 Langgikima; (2) to describe the forms of teacher exemplarity in developing discipline among students; and (3) to identify the obstacles and solutions in cultivating honest and disciplined character in students. This research employs a qualitative approach. Data were collected through observation, interviews, and documentation, while data validity was ensured using source triangulation and technique triangulation. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that: (1) the form of teacher exemplarity in fostering students’ honesty is implemented through the establishment of an “honesty canteen”; (2) the form of teacher exemplarity in fostering discipline is carried out through habit formation; (3) there are still inhibiting factors originating from the family and community environment; and (4) solutions to minimize these obstacles include personal approach and consistent habituation.